EFFECT OF THE USE OF MINERAL-VITAMIN COMPLEX IN DIETS OF GROWTH PERFORMANCE OF BOAR CROSS BREED IN WEANING PERIOD - S., Wenata; Siti, N W.; Utami, I. A. P. (Jurnal Peternakan Tropika, 2020)
This study aims to determine the effect of mineral-vitamin complex supplementation (pignox) in the ration to swine production performance race crosses weaning period. The study lasted 8 weeks in Banjar Lebah Jadi, Jadi Village, Kediri, Tabanan. The design used was a randomized block design (RBD) comprising 3 treatments and 4 replications. The treatments were attempted ration without supplementation of mineral-vitamin complex / pignox (A), supplementing the ration with 0.10% mineral-vitamin complex / pignox (B), and 0.20% ration supplemented mineral-vitamin complex / pignox (C) , The variables measured were final body weight, weight gain, feed intake and feed conversion ratio. The results were analyzed by analysis of variance and if there are significant differences (P <0, 5) then continued with Duncan's multiple range test (Steel and Torrie, 1991). The results showed that supplementation of mineral-vitamin complex at the level of 0.10% and 0.20% (P <0.5) can improve the final body weight, weight gain, improve feed intake and lower feed conversion ratio of boar cross breed in weaning period.   Keywords: supplementation, boar cross breed, production performance, pignox